Cochlear Implants and Remote Microphone Technology - Wolfe, Jace (Seminars in Hearing, 2014)
Advances in cochlear implant (CI) technology have allowed for impressive outcomes for implant recipients. In fact, many CI recipients achieve ceiling-level scores (i.e., near 100%) on sentence-recognition tests in quiet used in clinical settings. It is, however, well known that CI users often continue to experience difficulty with speech understanding in noisy and reverberant environments (e.g., classroom, restaurant, etc.). Recent research has indicated that performance in these difficult situations may be improved through the use of wireless remote microphone technology. In this article, a review will be provided of several studies that have explored the use of wireless remote microphones for CI users. Specifically, this review will focus on studies that have addressed both induction neckloop and directly coupled radiofrequency (RF) systems, fixed receiver gain settings, audio mixing ratio, adaptive frequency-modulated (FM) systems, cochlear implant signal processing, and digital RF systems. The effect of each of these items on a CI recipient's performance will be discussed. Additionally, clinical tips to optimize hearing assistance technology benefit for CI users will be provided as well as a protocol for fitting and verifying the appropriateness of wireless remote microphone technology for CI users and for optimizing user benefit.
Keywords: Autosensitivity control; cochlear implant; frequency modulation; input dynamic range; receiver gain; remote microphone radio frequency technology